26. OLAF’S SUITABILITY TO GLOBAL FINANCIAL CRIME GOVERNANCE ON COMBATING TRANSNATIONAL FINANCIAL CRIME IN EUROPEAN UNION (2011 – 2015) - Kamal, Reza Haidar; Putranti, Ika Riswanti; Basith Dir, Andi Akhmad (Journal of International Relations, 2016)
Frauds and corruptions are connective crimes considered to be extraordinary in manycountries. The damages are not limited to certain societies but could also bring harm tonational or even regional spheres. It raised awareness and leads to the inception of GlobalFinancial Crime Governance reflected in a number of international institutions i.e. FATF,UNCAC and OECD of which providing international standards of anti-fraud and anticorruptionbody. An institution currently in operation is European Union (EU)’s anti-fraudoffice known as OLAF, tasked to protect EU’s funds. This research aims to take a closerlook at OLAF and to examine the extent to which the institution has been suitable withGlobal Financial Crime Governance. To do so, this research highlight the imminentfeatures of common international bodies in combatting frauds and corruptions andafterwards will match the features on OLAF. These features come down to 6 respects: 1)Prevention; 2) Detection and Investigation; 3) Freezing, Seizing, Prosecution orConfiscation; 4) Cooperation; 5) Independence and Accountability; and 6) Asset recovery.This research reveals that OLAF has been suitable with the works of other internationalbodies evolving mostly on four of six common features.